2019
DOI: 10.1001/jamaoto.2018.2917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parental Perspectives and Concerns About Pediatric Tonsillectomy in Social Media

Abstract: Importance: Tonsillectomy is common in children, but little is known about parental preferences and values concerning this surgery. Social media offers a novel opportunity to evaluate parent understanding and experience of care. Objective: We systematically evaluate posts in a well-known social media site to identify parent perspectives about tonsillectomy in children that may not be apparent in a routine clinical encounter. Design: In this mixed methods analysis, we searched Twitter© for posts (“tweets”) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 48 publications
0
46
0
1
Order By: Relevance
“…Dimatos et al Similar changes in acoustic param-eters were observed in children undergoing postadenotonsillectomy and normalized in the third post-operative month (Dimatos et al, 2016). In a recent study, Hairston et al reported on parental concerns regarding tonsillectomy and about the importance of proper counseling of parents and further engaging them in making a proper decision on tonsillectomy for their child (Hairston et al, 2019). Our research will undoubtedly lead to this because our objective measurements demonstrated voice improvement after 3 and 6 weeks of surgery and can thus ease fears about post-operative voice changes.…”
Section: Resultsmentioning
confidence: 69%
“…Dimatos et al Similar changes in acoustic param-eters were observed in children undergoing postadenotonsillectomy and normalized in the third post-operative month (Dimatos et al, 2016). In a recent study, Hairston et al reported on parental concerns regarding tonsillectomy and about the importance of proper counseling of parents and further engaging them in making a proper decision on tonsillectomy for their child (Hairston et al, 2019). Our research will undoubtedly lead to this because our objective measurements demonstrated voice improvement after 3 and 6 weeks of surgery and can thus ease fears about post-operative voice changes.…”
Section: Resultsmentioning
confidence: 69%
“…A recent study identified that over 90% of parents use social media to find out more about their child’s cleft lip/palate diagnosis and treatment options and use it to guide decisions (Khouri et al, 2018). A 2019 study that examined parents’ tweets about pediatric tonsillectomy found that parents tweeted about procedural concerns and the tonsillectomy experience (Hairston et al, 2019). In our study, parents authored just 3% of all tweets, suggesting that they may take more of a passive role on Twitter when it comes to cleft lip/palate.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent was waived by the Johns Hopkins Institutional Review Board because all of the data were posted publicly online. The methodology our study follows a protocol similar to that of the 2019 Hairston et al 31 social media study that used Twitter.com to evaluate parental perspectives of their child’s tonsillectomy. The search strategy was devised using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) method of reporting systematic literature reviews.…”
Section: Methodsmentioning
confidence: 99%